2016
DOI: 10.1021/acsami.6b05791
|View full text |Cite
|
Sign up to set email alerts
|

200 GHz Maximum Oscillation Frequency in CVD Graphene Radio Frequency Transistors

Abstract: Graphene is a promising candidate in analog electronics with projected operation frequency well into the terahertz range. In contrast to the intrinsic cutoff frequency (f) of 427 GHz, the maximum oscillation frequency (f) of graphene device still remains at low level, which severely limits its application in radio frequency amplifiers. Here, we develop a novel transfer method for chemical vapor deposition graphene, which can prevent graphene from organic contamination during the fabrication process of the devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 30 publications
2
70
0
Order By: Relevance
“…The highest measured extrinsic was 21.3 GHz in a GFET with W  = 10  μ m and L  = 1  μ m (discussion on the intrinsic can be found in the Supplementary information). The obtained values are comparable to those of GFETs with the same gate length 14, 16, 28 . Even though it has previously been found that does not scale very well with the gate length in GFETs 28 , we observed a gate-length dependence down to 0.8  μ m, despite noticeable degradation in submicron devices.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…The highest measured extrinsic was 21.3 GHz in a GFET with W  = 10  μ m and L  = 1  μ m (discussion on the intrinsic can be found in the Supplementary information). The obtained values are comparable to those of GFETs with the same gate length 14, 16, 28 . Even though it has previously been found that does not scale very well with the gate length in GFETs 28 , we observed a gate-length dependence down to 0.8  μ m, despite noticeable degradation in submicron devices.…”
Section: Resultssupporting
confidence: 74%
“…As a consequence, the output conductance ( g d ) was reduced well below 50 S/m (normalized by the channel width W ) leading to very large values of the open-circuit voltage gain A v  > 30 dB and forward gain S 21  = 12.5 dB (at 10 MHz) in GFETs with the channel widths W  = 10  μ m and W  = 100  μ m, respectively, which are the highest gains measured in GFETs so far 9–12 . This low output conductance also contributed to a large ratio between the extrinsic maximum oscillation frequency ( f max ) and cutoff frequency ( f T ) of ~3, which is unusually high for GFETs, in which f max / f T typically ranges from <1 13, 14 to ~1.5 15, 16 to 3.3 17 . However, the highest measured extrinsic f max was 21.3 GHz highlighting the need for alternative substrates with less charge traps 14 and cleaner graphene transfer process 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, both contact resistance and channel resistance make contribution to output resistance of GFET. A polymeric residue-free graphene fabrication process50 can be carried out to reduce contact resistance. Channel resistance can be decreased by fabricating GFET with nanoscale channel length and large W/L ratio.…”
Section: Resultsmentioning
confidence: 99%
“…As potential carrier mobility of graphene is extremely high, the operation bandwidth of GPD is limited by RC constant of the device structure and a 500 GHz [21] intrinsic operation speed can be achieved in the future. Although the first graphene-based optical receiver achieved in this work just works at 500 kHz with 1550 nm carrier waves, the performance can be improved significantly if a single crystal graphene with higher carrier mobility is used and an optimized fabrication process [45] is carried out to reduce contact resistance and remove residue on the graphene surface. In addition, further collaborative parameter optimization of the TIA chips and GPDs may increase the operation speed to a great extent.…”
Section: Discussionmentioning
confidence: 99%